Picard-Vessiot theory of differentially simple rings - Maurischat, Andreas (Journal of algebra, 2014)
Having in mind that the classical Galois theory is a theory of extensions of fields, i.e. of simple rings, it is quite natural to ask whether one can also set up a Picard-Vessiot theory where the base is not a differential field, but more generally a differentially simple ring. It is the aim of this article to give a positive answer to this question, i.e. to set up such a differential Galois theory.